Prediksi Jumlah Kasus Schistosomiasis Di Kabupaten Poso Sulawesi Tengah - Ulan Rahmawati; Resnawati; Maulidyani Abu; Puspita, Juni Wijayanti (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2023)
The prevalence of Schistosomiasis cases in Poso Regency specifically in Napu and Bada changes every year and in 2021 there was a significant increase in cases. Therefore it is necessary to predict cases in 2022 or the 13th and 14th semesters using Lagrange extrapolation. The prediction results of the cases number in Napu in 13th and 14th semesters are 461 and 5445 for humans, 12442 and 43045 for snails, and 1370 and 4789 for rats respectively. The prediction results in Bada in the 13th and 14th semesters are 202 and 984 cases for humans, -804 and -2863 cases for snails, and -251 and -890 cases for rats respectively. The Lagrange polynomial errors are −0,16335 × 10−5 and −0,8629 × 10−5 for the 13th and 14th semesters for humans, 0,578 × 10−7 and 0,2288 × 10−7 the for 13th and 14th semesters for snails and rats. Some of the predictions were unrealistic, so the Lagrange extrapolation method is not appropriate for predicting Schistosomiasis cases.